2022
DOI: 10.3390/life12101557
|View full text |Cite
|
Sign up to set email alerts
|

C-Reactive Protein as a Potential Peripheral Biomarker for High-Lethality Suicide Attempts

Abstract: The aim of the present study was to identify a cut-off of c-reactive protein (c-RP) potentially predictive of high-lethality suicide attempts (SA) in an inpatient psychiatric sample. After attempting suicide, subjects were admitted to the emergency ward of the IRCCS Ospedale Policlinico San Martino and later to the section of Psychiatry from 1st August 2013 to 31st July 2018. C-reactive protein was measured. The Area Under the Receiver Operating Characteristic (ROC_AUC) was used to assess the discriminative ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Of course, pointing out distinct molecules that could serve as markers for assessing suicide risk is not so immediate. In fact, findings of immune dysregulation in suicidal patients are not uniform, but, in the literature that we analyzed, IL-6 and CRP were the most significantly altered inflammatory parameters [101,102,105,106]. Moreover, studies that show the possibility of a direct correlation between inflammation and suicide (without the mediating effect of depressive symptomatology) are maybe the most interesting from our point of view [104,105].…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Of course, pointing out distinct molecules that could serve as markers for assessing suicide risk is not so immediate. In fact, findings of immune dysregulation in suicidal patients are not uniform, but, in the literature that we analyzed, IL-6 and CRP were the most significantly altered inflammatory parameters [101,102,105,106]. Moreover, studies that show the possibility of a direct correlation between inflammation and suicide (without the mediating effect of depressive symptomatology) are maybe the most interesting from our point of view [104,105].…”
Section: Discussionmentioning
confidence: 89%
“…Thus, suicide appears to be correlated with higher inflammation levels both in the CNS (as indicated by the analysis of cerebrospinal fluid) and in the periphery. Regarding peripheral inflammation, Aguglia et al [102], in study conducted among a sample of 432 hospitalized suicide attempters, found a higher level of CRP within high-lethality cases and also among suicide re-attempters [103]. Interestingly, the aim of this work was to set a cut-off of CRP that should have a significant predictive value for a high-lethality suicide attempt.…”
Section: E-chronotypes and Suicidality: Immune Dysregulation As A Fur...mentioning
confidence: 89%
“…The association between psychological and inflammatory markers has been widely studied [ 3 , 4 , 5 , 6 , 7 , 8 ]; this association has been explained as a bilateral relationship between psychic suffering and inflammation, with some reports showing that inflammation is related to the appearance of depression and suicidal behavior [ 27 , 28 ]. This relationship has also been observed in long-COVID cases, where neuropsychiatric sequelae have been observed in response to hyper and neuroinflammation [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we did not observe differences between the degree of lethality in individuals with suicide attempts. One previous study reported an association between suicide attempt lethality and other biomarkers suggesting the C-reactive protein as a peripheral biomarker; however, measuring the IL-6 levels was not within the study objectives [ 6 ]. Similarly, the total cholesterol, high LDL-c, HDL-c, and triglycerides have been associated with the lethality of suicide attempts [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Each year, approximately 700,000 people die by suicide [ 3 ]. It is estimated that, for every completed suicide, there are around 20 suicide attempts worldwide; nonetheless, some reports indicate that some countries have higher rates of suicide fatalities, as 8.5–13% of all suicide attempts are fatal [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%